IMPROVING THE ACCOUNTING, ANALYSIS AND AUDIT OF FINANCIAL RESULTS BY TYPES OF ACTIVITY OF ORGANIZATIONS IN UZBEKISTAN - Abdurashidov Faxriddin Fazliddin o‘g‘li; Beknazarov Zafarjon Ergachevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article investigates the improvement of accounting, analysis and audit of financial results by types of activity in organizations, using Uzbekistan as a case study. The paper examines the methodology for recording revenues and expenses under operating, investing and financing activities in accordance with IFRS and Uzbekistan National Accounting Standards (NAS), and explores the application of DuPont decomposition, variance analysis and NPV methods in assessing financial performance. Using official data from the State Statistics Committee of the Republic of Uzbekistan for 2021–2025, the dynamics of enterprise financial results are analysed. The article concludes with recommendations for enhancing the effectiveness of audit procedures and ensuring transparency in financial reporting.